Evaluating corporate reporting on the internet: the case of zakat institutions in Malaysia - Shamharir Abidin; Ram Al Jaffri Saad; Nikmal Muzal Mohd Muhaiyuddin (Penerbit Universiti Kebangsaan Malaysia, 2014)
The purpose of this study is to document the extent of financial and non-financial reporting practices through the internet by zakat institutions and to identify the type of information reported. Using a checklist adapted from similar studies in the commercial sector, the study suggests that the disclosures of financial and non-financial information such as information on social responsibility are uncommon. While most of the zakat institutions focus on providing information regarding zakat collection and distribution, none has included financial statements. However, these institutions have gained reasonable score in terms of information timeliness with majority of them update their website on regular basis. The findings suggest that zakat institution in Malaysia should fully utilise the use internet as a main medium of communication, especially in order to gain more public trust and recognition.